2011
DOI: 10.1080/09588221.2010.536952
|View full text |Cite
|
Sign up to set email alerts
|

A mobile-assisted synchronously collaborative translation–annotation system for English as a foreign language (EFL) reading comprehension

Abstract: This research introduced mobile devices into an intensive reading course and allowed functions that are usually found only in the language laboratory to be easily and flexibly utilized in the general classroom. To enhance and improve the reading comprehension of English as a foreign language (EFL) readers, a computer-assistedlanguage-learning (CALL) system for use on PDAs, integrating an instant translation mode, an instant translation annotation mode, and an instant multiusers shared translation annotation fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 23 publications
7
90
0
Order By: Relevance
“…Concerning other variables of TAM, previous studies have suggested that PEU may significantly influence PU [43]; however, Saadé and Bahli [44] as well as Sá nchez and Hueros [6] did not find support for such a claim. Thus, the present research proposes further hypotheses on the effect of PEU on PU, and both of these on attitudes towards CALL, formulated as follows:…”
Section: A Proposed Model and Research Hypothesesmentioning
confidence: 91%
“…Concerning other variables of TAM, previous studies have suggested that PEU may significantly influence PU [43]; however, Saadé and Bahli [44] as well as Sá nchez and Hueros [6] did not find support for such a claim. Thus, the present research proposes further hypotheses on the effect of PEU on PU, and both of these on attitudes towards CALL, formulated as follows:…”
Section: A Proposed Model and Research Hypothesesmentioning
confidence: 91%
“…In terms of the remaining variables of TAM, some studies postulate that PEU may significantly influence PU [19], whereas the results of other studies do not support such a claim [20], [21]. Therefore, it is noteworthy to extend our current understanding on the association of these two variables, particularly in the context of using M-Learning in hospitality courses.…”
Section: A Proposed Model and Research Hypothesesmentioning
confidence: 94%
“…Students´ feedback was expressed on the six-level scale from 1 -completely agree to 6 -completely disagree. In other words, this evaluation questionnaire focused on the field how the mobile technology was viewed by individual users within the MALL process (Chang, Hsu, 2011;Cheng et al, 2010). For the future research activities the main objective will be to learn in what ways the use of mobile devices facilitates the acquisition and development of linguistic knowledge and language skills.…”
Section: Methodsmentioning
confidence: 99%